The Development of Cultural Immunity in Students Based On an Individualized Approach (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept of cultural immunity refers to an individual's ability to resist negative influences while adapting to the cultural environment. For students, who are in a critical phase of their personal and academic development, the ability to develop cultural immunity plays a vital role in their integration into society and the globalized world. This paper explores the process of developing cultural immunity in students, emphasizing the significance of an individualized approach. The research examines key factors influencing the development of cultural immunity, including personal values, social context, educational methods, and psychological adaptability. Moreover, it highlights the role of educators and institutions in fostering cultural immunity through tailored programs and strategies. The study concludes with recommendations for effective educational practices that contribute to the formation of cultural immunity in students.